Vortex dynamics and turbulence in dipolar Bose-Einstein condensates - Sabari, S. [UNESP]; Kishor Kumar, R. [UNESP]; Tomio, Lauro [UNESP] (American Physical Society (APS), 2024)
Quantum turbulence indicators in dipolar Bose-Einstein condensed fluids, following emissions of vortex-antivortex pairs generated by a circularly moving detuned laser, are being provided by numerical simulations of the corresponding quasi-two-dimensional Gross-Pitaevskii formalism with repulsive contact interactions combined with tunable dipole-dipole strength. The critical velocities of two variants of a circularly moving obstacle are determined and analyzed for vortex-antivortex nucleation in the form of regular and cluster emissions. The turbulent dynamical behavior is predicted to follow closely the initial emission of vortex-antivortex pairs, relying on the expected Kolmogorov classical scaling law, which is verified by the spectral analysis of the incompressible part of the kinetic energy. Within our aim to provide further support in the investigations to date of quantum turbulence, which have been focused on nondipolar Bose-Einstein condensates, we emphasize the role of dipole-dipole interactions in the fluid dynamics.